A Cross-sectional Study on Hepatitis B Immune Status Among Vaccinated Healthcare Workers in Khartoum, Sudan - Abdullahi Elsheikh Mahgoub; Yassir Hamadalnil; Osama Mohammed; Rasha Nakhleh; Musa Mohamed Khair (Sudan Journal of Medical Sciences, 2020)
Background: Hepatitis B virus (HBV) infection can lead to chronic hepatitis, liver cirrhosis, and Hepatocellular Carcinoma (HCC). Vaccination against the virus plays an important role in its prevention. Health personnel at risk of infection are recommended to receive the vaccine and to check their immune status thereafter. Objective: To determine Hepatitis B Immune status among vaccinated health personnel in Khartoum state, Sudan. A total of 106 health personnel from different hospitals and doctors’ mess in Khartoum and from different jobs were surveyed and their HBV surface antibodies levels were determined by HBsAb (Quantitative) ELISA Kits. Methods: Of the 106 participants in this study, the majority were females 72.6%. The mean age of those involved was 27.69 years, and nurses made for more than 50% of those surveyed. About 56.6% (60) of the health personnel involved took three or more doses of HBV vaccine while the rest received one or two doses. The results of the participants who received three or more doses of the vaccine represented immunity by 70%. In general, about 47.2% (50) of the participants in this study did show excellent immune response (>100 mIU/mL) and 18.9% (20) had weak protective levels (between 10 and 100 mIU/mL) So, we concluded that HBV post-vaccination immunity status of health personnel in Khartoum state is lower than post-vaccination HBV immunity in other parts of the world. There is an urgent need for a national protocol of HBV vaccination to improve the immunization status of health personnel with a regular checkup of HBV immunity and easy access to a good-quality vaccine.